Structural changes of ethanolamine plasmalogen during intestinal absorption. Issue 9 (27th August 2020) - Takahashi, Takumi; Kamiyoshihara, Reina; Otoki, Yurika; Ito, Junya; Kato, Shunji; Suzuki, Takuji; Yamashita, Shinji; Eitsuka, Takahiro; Ikeda, Ikuo; Nakagawa, Kiyotaka
Abstract : A part of ethanolamine plasmalogen (PE-Pls) undergoes structural changes ( i.e., arachidonic acid re-esterification and base conversion of PE-Pls into choline plasmalogen (PC-Pls)) during intestinal absorption. Abstract : Considerable attention has been paid to the absorption mechanisms of plasmalogen (Pls) because its intake has been expected to have preventive effects on brain-related diseases. Possible structural changes of Pls during absorption ( i.e., preferential arachidonic acid re-esterification at the sn -2 position and base conversion of ethanolamine Pls (PE-Pls) into choline Pls (PC-Pls)) have previously been proposed. Since the physiological functions of Pls differ according to its structure, further elucidation of such structural changes during absorption is important to understand how Pls exerts its physiological effects in vivo . Hence, the absorption mechanism of Pls was investigated using the lymph-cannulation method and the everted jejunal sac model, with a focus on Pls molecular species. In the lymph-cannulation method, relatively high amounts of PE-Pls 18:0/20:4 and PC-Pls 18:0/20:4 were detected from the lymph even though these species were minor in the administered emulsion. Moreover, a significant increase of PE-Pls 18:0/20:4 and PC-Pls 18:0/20:4 in the intestinal mucosa was also confirmed by the everted jejunal sac model. Therefore, structural changes of PE-Pls in the intestinal mucosa were strongly suggested. The results of this study may provide an understanding of the relationship between intestinal absorption of Pls and exertion of its physiological functions in vivo .